How Does Ocean Acidification Affect the Early Life History of Zostera marina? A Series of Experiments Find Parental Carryover Can Benefit Viability or Germination - Lowell, Alyson; Infantes, Eduardo; West, Laura; Puishys, Lauren; Hill, Claudia E. L.; Ramesh, Kirti; Peterson, Bradley; Cebrian, Just; Dupont, Sam; Cox, T. Erin (Frontiers in Marine Science, 2021)
Elevated partial pressure of carbon dioxide (pCO2) as a concomitant of global climate change may facilitate the establishment of future seagrass meadows and subsequently its benefit could be incorporated into techniques to increase restoration success. In five manipulative experiments, we determined how increased CO2 affects the maturation of flowers, and the development of seeds and seedlings for the foundation species Zostera marina. Experiments tested the development from both seeds collected from non-treated flowering shoots (direct) and seeds harvested from flowering shoots after CO2 exposure (parental carryover). Flowering shoots were collected along the western coast of Sweden near the island of Skafto. The seeds produced were used in experiments conducted at Kristineberg, Sweden and Dauphin Island, Alabama, USA. Experiments varied in temperature (16, 18 ºC) and salinity (19, 33 ppt), as well as duration and magnitude of elevated CO2 exposure. Environmental conditions among experiments, such as temperature (16, 18 ºC) and salinity (19, 33 ppt), as well as duration and magnitude of pCO2 exposure differed. Flowering maturation, spathe number, seed production, and indicators of seed quality did not appear to be affected by 39 to 69 days of exposure to CO2 conditions outside of natural variability (pCO2 = 1547.2 ± 267.60 µatm; pHT = 7.53 ± 0.07). Yet, seeds produced from these flowers showed 2-fold greater germination success. In another experiment, flowering shoots were exposed to an extreme CO2 condition (pCO2 = 5950.7 ± 1849.82 µatm; pHT = 6.96 ± 0.15). In this case, flowers generated seeds that demonstrated a 5-fold increase in an indicator for seed viability (sinking velocity). In the latter experiment, however, germination appeared unaffected. Direct CO2 effects on germination and seedling production were not observed. Our results provide evidence of a parental CO2 effect that can benefit germination or seed viability, but early benefits may not lead to bed establishment if other environmental conditions are not well suited for seedling development. Outcomes have implications for restoration; CO2 can be supplied to flowering shoot holding tanks to bolster success when the purpose is to redistribute seeds to locations where beds are extant and water quality is adequate.